2023
DOI: 10.1007/s12144-023-04783-y
|View full text |Cite
|
Sign up to set email alerts
|

Preschool children’s screen time during the COVID-19 pandemic: associations with family characteristics and children’s anxiety/withdrawal and approaches to learning

Abstract: With schools closed due to the COVID-19, many children have been exposed to media devices for learning and entertainment, raising concerns over excessive screen time for young children. The current study examined how preschoolers’ screen time was associated with their family characteristics and anxiety/withdrawal and approaches to learning during the COVID-19 pandemic. Participants were 764 caregivers of 3- to 6-year-old children (mean age = 59.07 months, SD = 12.28 months; 403 boys and 361 girls) from nine pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…Isolation and an increase in sedentary lifestyles have played a key role in the development of excess weight among this demographic [ 15 , 16 , 17 , 18 ]. Moreover, it has been noticed that after the COVID-19 outbreak, screen time among children increased [ 19 , 20 ]. A recent report published by the CDC demonstrated that in the pediatric population in the United States between the pre-pandemic period and during the COVID-19 pandemic, the rate of body mass index almost doubled from 0.052 (95% CI = 0.051–0.052) to 0.100 (95% CI = 0.098–0.101) kg/m 2 /month [ 1 ].…”
Section: The Impact Of Chronic Stress Related To the Covid-19 Pandemi...mentioning
confidence: 99%
“…Isolation and an increase in sedentary lifestyles have played a key role in the development of excess weight among this demographic [ 15 , 16 , 17 , 18 ]. Moreover, it has been noticed that after the COVID-19 outbreak, screen time among children increased [ 19 , 20 ]. A recent report published by the CDC demonstrated that in the pediatric population in the United States between the pre-pandemic period and during the COVID-19 pandemic, the rate of body mass index almost doubled from 0.052 (95% CI = 0.051–0.052) to 0.100 (95% CI = 0.098–0.101) kg/m 2 /month [ 1 ].…”
Section: The Impact Of Chronic Stress Related To the Covid-19 Pandemi...mentioning
confidence: 99%